Modulatory effects of ethanol extract of Dissotis rotundifolia whole plant on metabolic syndrome-induced hepato-renal dysfunctions in rats (Nigerian Journal of Physiological Sciences, 2025)
Metabolic syndrome has been associated with the incidence of liver and chronic kidney damage. This study aimed at exploring the mitigatory action of Dissotis rotundifolia whole plant extract on metabolic syndrome-induced hepato-renal dysfunctions. Fifty (50) adult male Wistar rats weighing between 150-180 g were randomly distributed into groups of ten rats each as follows: Group 1 (Control), Group 2 (MetS control), Group 3 (MetS + 100 mg/kg ethanol extract of Dissotis rotundifolia), Group 4 (MetS + 200 mg/kg ethanol extract of Dissotis rotundifolia), and Group 5 (MetS + 20 mg/kg Rosuvastatin). Metabolic syndrome was established by feeding the rats with high carbohydrate (10 -20% fructose) in drinking water and high fat-induced diet (20 - 40%) for 8 weeks. Biomarkers of hepatic and renal damage, oxidative stress, antioxidant parameters, lipid profiles, and immunohistochemistry of the liver and kidney tissues of rats were determined. The results showed that metabolic syndrome caused a significant increase in biomarkers of oxidative stress malondialdehyde (MDA), hydrogen peroxide (H2O2) generation, Low Density Lipoprotein cholesterol (LDL-c), High Density Lipoprotein cholesterol (HDL-c), Triglycerides (TG), Total Cholesterol (TC), but significantly reduced hepatic and renal glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione S-transferase (GST) in comparison with the control.  Furthermore, biomarkers of renal and hepatic damage were significantly elevated in MetS untreated rats. Higher renal immune-reactivity of Neutrophil Gelatinase-Associated Lipocalin (NGAL) but lower expression of Angiotensin Converting Enzyme (ACE) was recorded for MetS untreated rats. Dissotis rotundifolia extractmitigated biomarkers of oxidative stress, hepato-renal dysfunctions, and improved antioxidant defense system. The observed protective effects of Dissotis rotundifolia on metabolic syndrome-induced hepatic and renal damage could be due to amelioration of lipid peroxidation and increased antioxidant defense system.